2021
DOI: 10.1016/j.jmii.2020.06.006
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 host diversity: An update of natural infections and experimental evidence

Abstract: caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is now a pandemic threat. This virus is supposed to be spread by human to human transmission. Cellular angiotensin-converting enzyme 2 (ACE2) is the receptor of SARS-CoV-2 which is identical or similar in different species of animals such as pigs, ferrets, cats, orangutans, monkeys, and humans. Moreover, a recent study predicted that dogs might be secondary hosts during the evolution of SARS-CoV-2 from bat to human. Therefore, there is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
78
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 46 publications
1
78
0
3
Order By: Relevance
“…The animal host range of SARS-CoV-2 has been predicted by sequence analysis and structure simulation studies [15,16]; however, not all key residues at the SARS-CoV-2-ACE2 interface, but rather only a limited number of them, have been considered in these studies. Evidence of SARS-CoV-2 infection in animals was reviewed while this article was under revision [17,18]. Lagomorphs may act as an important wildlife reservoir for zoonotic viruses.…”
Section: Introductionmentioning
confidence: 99%
“…The animal host range of SARS-CoV-2 has been predicted by sequence analysis and structure simulation studies [15,16]; however, not all key residues at the SARS-CoV-2-ACE2 interface, but rather only a limited number of them, have been considered in these studies. Evidence of SARS-CoV-2 infection in animals was reviewed while this article was under revision [17,18]. Lagomorphs may act as an important wildlife reservoir for zoonotic viruses.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is reported that diseased humans have transmitted the virus naturally to ferrets, cats, dogs, tigers, lion and minks [ 3 , [56] , [57] , [58] , [59] ].Apart from minks farms, there is no evidence so far that livestock for human consumption such as cows, sheep and pigs have been infected in farms [ 60 ]. This last point is rather important if it is considered that in the case of MERS-CoV, which belongs to Coronaviridae beta subfamily like SARS-CoV-2 but not to the subgenus Sarbecovirus, camels [ 61 , 62 ] were suspected to be possible reservoirs or intermediate hosts for successive outbreaks.…”
Section: Sars-cov-2 Zoonosismentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID-19) caused by SaRS-CoV-2 (Severe acute respiratory syndrome coronavirus-2) became a pandemic threat and serious public health emergency of international concern in the winter of 2019-20 1 . Though COVID-19 was reported for the first time on December 31, 2019 in Wuhan, China, the disease has spread very rapidly throughout the world due to its extremely high contagiousness 2,3 . The clinical symptoms of COVID-19 are mild to high fever, cough, fatigue, dyspnea, headache, and diarrhea, which depend on the age and condition of the infected patients 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…Though COVID-19 was reported for the first time on December 31, 2019 in Wuhan, China, the disease has spread very rapidly throughout the world due to its extremely high contagiousness 2,3 . The clinical symptoms of COVID-19 are mild to high fever, cough, fatigue, dyspnea, headache, and diarrhea, which depend on the age and condition of the infected patients 3,4 . However, the number of confirmed cases of COVID-19 is increasing worldwide due to human to human transmission, lack of vaccine, and antiviral drugs against SARS-CoV-2 2,3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation